2010
DOI: 10.1530/rep-10-0075
|View full text |Cite
|
Sign up to set email alerts
|

Sex determination in mammalian germ cells: extrinsic versus intrinsic factors

Abstract: Mammalian germ cells do not determine their sexual fate based on their XX or XY chromosomal constitution. Instead, sexual fate is dependent on the gonadal environment in which they develop. In a fetal testis, germ cells commit to the spermatogenic programme of development during fetal life, although they do not enter meiosis until puberty. In a fetal ovary, germ cells commit to oogenesis by entering prophase of meiosis I. Although it was believed previously that germ cells are pre-programmed to enter meiosis u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(81 citation statements)
references
References 159 publications
(174 reference statements)
1
78
0
2
Order By: Relevance
“…In contrast, another pluripotencydetermining factor, NANOG, was expressed exclusively in marmoset ES cells and testis. Among the germ cell marker genes, PRDM1, DPPA3 (STELLA), and IFITM3, which are expressed predominantly during the PGC stages in mouse development (Ohinata et al 2008, Bowles & Koopman 2010, displayed significant expression in marmoset testis. Indeed, these genes were only expressed at faint or undetectable levels in mouse testis (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, another pluripotencydetermining factor, NANOG, was expressed exclusively in marmoset ES cells and testis. Among the germ cell marker genes, PRDM1, DPPA3 (STELLA), and IFITM3, which are expressed predominantly during the PGC stages in mouse development (Ohinata et al 2008, Bowles & Koopman 2010, displayed significant expression in marmoset testis. Indeed, these genes were only expressed at faint or undetectable levels in mouse testis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, in the current study, we identified the following expression profiles that distinguish marmoset testis from mouse testis: POU5F1K/NANOGC/PRDM1C/DPPA3C/IFITM3C /ZP1C in marmoset and Pou5f1C/NanogK/Prdm1K /Dppa3K/Ifitm3K/ZP1K in mouse (Figs 1 and 2). Compared with mouse, marmoset testis tended to express genes whose homologs in mouse are known as typical markers at an earlier developmental stage, as shown by the expression of the migratory PGC markers NANOG, PRDM1, DPPA3, and IFITM3 (Ohinata et al 2008, Bowles & Koopman 2010. A recent report also demonstrated that prepubertal human spermatogonia exhibit an expression profile similar to that of mouse gonocytes (Wu et al 2009).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In an ovary, PGCs enter the first meiotic prophase, while in a testis they enter mitotic arrest (Bullejos & Koopman 2004, Western et al 2008. XX and XY germ cells were believed to not be sexually dimorphic until this differentiation process is initiated by their surrounding cells, testicular or ovarian somatic cells (Bowles & Koopman 2010). This view has been challenged by two reports demonstrating sexually dimorphic gene expression in PGCs long before initiation of meiosis in an ovary and mitotic arrest in a testis.…”
Section: The Differentiation Of Pgcs In Mammalsmentioning
confidence: 99%
“…Cytological analysis in mice and human suggests that both female and male PGCs are equally capable of entering meiosis (12 dpc in mice and 10 weeks in humans) and that the decision of cell fate of germ cells, either meiosis or mitosis takes place in the gonad (McLaren and Southee, 1997;Suzuki and Saga, 2008;Bowles and Koopman, 2010). It is still unknown and controversial whether entry into meiosis is induced in the female gonad or whether it is intrinsically programmed in both male and female PGCs and inhibited in the male gonad and permissive in the female gonad, or whether it is due to a combination of regulatory factors.…”
Section: Fetal Samplesmentioning
confidence: 99%